Mesoclimatic analysis of non-precipitation periods in Lithuania - Ūselytė, Joana; Bukantis, Arūnas (Journal of Environmental Engineering and Landscape Management, 2023)
In this paper, climatic analysis of non-precipitation periods (NPP) in Lithuania was performed, assessing their recurrence and trends from 1991 to 2020 using two criteria – when precipitation was <0.1 mm per day all year round and when precipitation was <1 mm per day during the warm period – and analysing typical atmospheric circulation in the middle troposphere and sea level during the longest NPP (≥20 days). From 1990 to 2020, NPP were most frequent in the Middle Lithuania lowland (according to both criteria), in Southern and South-western Lithuania (daily precipitation <0.1 mm) and in part of Eastern Lithuania (daily precipitation <1 mm), and least frequent in part of the Samogitian highland and in part of the Baltic Highlands (according to both criteria). NPP recurred most often in the spring months, as this is associated with a higher number of days with anticyclonic circulation and powerful anticyclones recorded. Based on the growth trend of NPP of various durations in Lithuania from 1990 to 2020, in the last decade NPP have become more frequent, but only a few stations have shown reliable trends. Analysis of the atmospheric circulation during the longest NPP (≥20 days) showed that NPP were mostly determined by the Azores anticyclone ridge or anticyclone over Northern, Central or Eastern Europe regardless of the time of year. The atmospheric circulation conditions for the formation of long NPP varied more in the cold period than in the warm period, but NPP often lasted ≥20 days only at one or a few stations.